Pengaruh Lingkungan Kerja Non Fisik, Kompensasi Non Finansial, Kepuasan Kerja, Motivasi Kerja, dan Budaya Organisasi terhadap Loyalitas Karyawan pada PT. Kencana Amal Tani PKS – Seberida - Yudi Adrian; Sonnya Marliani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
His study aims to analyze the influence of the non-physical work environment, non-financial compensation, job satisfaction, work motivation, and organizational culture on employee loyalty at PT. Kencana Amal Tani PKS – Seberida. The study population consisted of all 98 factory employees, all of whom were included in the sample (census method). Data analysis was conducted using multiple linear regression with the aid of SPSS version 25. The results indicate that, simultaneously, the five independent variables have a positive and significant effect on employee loyalty (F-calculated = 52.345 > F-table = 2.31; Sig. 0.000). Individually, each variable also exerts a positive and significant influence, with work motivation being the most dominant variable (beta = 0.268; t-calculated = 3.551). The R-Square value of 0.769 indicates that 76.9% of the variation in employee loyalty can be explained by these five variables, while the remaining 23.1% is explained by variables outside the model. These findings confirm that improvements in the non-physical work environment, non-financial compensation, job satisfaction, work motivation, and organizational culture will collectively enhance employee loyalty. The study recommends that the company prioritize boosting work motivation through recognition, challenging work, and a supportive environment, as well as strengthening an organizational culture based on togetherness and integrity.